PENGARUH KINERJA LINGKUNGAN TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2017 - 2021 - Zonarico Karo-Karo; Aditya Amanda Pane; Ali Usman (CV. Armas Suan Sejahtera, 2024)
The purpose of this research is to determine the influence of environmental performance on company value in companies listed on the BEI in 2017-2021, partially and simultaneously. The research population is all companies that participated in Proper from 2017-2021 and were listed on the Indonesia Stock Exchange (BEI) from 2017-2021. with a sampling technique based on criteria using purposive sampling. The samples obtained were based on the criteria of 16 companies listed on the Indonesian Stock Exchange. The type of research is quantitative with a causal associative approach. The data analysis technique used is quantitative with descriptive statistics using SPSS v.25. Based on the results of the partial test, the following equation can be formulated as the t-calculated value (4.710) > t-table (1.99) and sig value (0.000) < 0.05 so it can be concluded that environmental performance